Taxpayers’ rights - Bentley, Duncan (Kluwer Law International,Sold and distributed in North, Central and South America by Aspen Publishers, 2007)
The theory and framework of taxpayers’ rights to provide support and reassurance for particular approaches to tax administration design; the updated principles for analysis of any tax system; the classification of taxpayers’ rights so that they can understand why much tax administration and procedure operates in the way it does; the design of legislative mechanisms to assist in the design and drafting of tax administration; the design and implementation of dispute resolution systems in tax administration; specific detail on the powers and duties of tax administrators and how they should be exercised; the design and implementation of taxpayers’ charters and other guidelines on taxpayers’ rights; specific detail on the rules and procedures in tax administration, relating in any way to taxpayers’ rights, and how they should be applied; and a clear and articulated standard of best practice in tax administration and governance for quality assurance purposes.